Pemanfaatan Konten Visual Instagram dalam Meningkatkan Brand Awareness Premiair Group - Septiani, Nur Afni; Priatna, Wahyu Budi (Universitas Prof. Dr. Moestopo (Beragama), 2026)
This study aims to analyze the Instagram visual content strategy implemented by Premiair Group in enhancing brand awareness through the AIDA (Attention, Interest, Desire, Action) model. The research employs a descriptive qualitative approach with a case study method, utilizing in-depth interviews with the Marketing Communication team and secondary data analysis. The findings indicate that the visual content strategy is systematically developed based on established brand guidelines, with a strong emphasis on the consistent use of color palette as the company’s primary visual identity. The implementation of the AIDA model is reflected in attention-grabbing visual elements, the delivery of relevant and distinctive information, the construction of emotional appeal, and the provision of clear call-to-action through accessible contact information. The novelty of this study lies in its analytical focus on the company’s perspective in managing AIDA-based visual content strategies within the private aviation industry, which remains underexplored in academic discourse. The academic contribution of this research is to enrich the literature on digital marketing communication, particularly in relation to the application of the AIDA model in social media visual strategies to build brand awareness in premium service industries.